Consideration of hotspots in the selection of supervision schemes to reduce illegal dumping of construction and demolition waste - Barakat, Boushra (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2024)
Illegal dumping of construction and demolition waste continues to be a problem hindering circular economy efforts. Controlling illegal dumping necessitates establishing an effective surveillance scheme and investigating the proper penalty value. This problem has previously been described as a game theory problem, with the government and construction contractors as the players. Taking into account illegal dumping hotspots, which can often be identified through topographical and geographical characteristics, is also important when establishing supervision strategies. This study develops an evolutionary game-theoretic model that can assist in devising effective supervision strategies to control the spread of illegal dumping, while taking into consideration hotspots. In specific, this study investigates the suitability of two alternative strategies: police patrols and hybrid monitoring through both patrols and the installation of closed-circuit television cameras in hotspots. The model was applied to two case studies, using parameters informed by real-world contexts, to demonstrate its potential for selecting suitable strategies according to local situations. The results suggest that nine possible scenarios govern the stable evolutionary strategies of game players, with five scenarios in which contractors converge to adopt legal dumping. Accordingly, based on the parameters of the region (hotspot areas, cost of supervision, efficiency of patrols, penalties, etc.), governments would be able to assess which of the strategies would lead to long-term compliance of contractors while also increasing their payoffs. Further analysis allowed to determine the minimum efficiency required, and simulations were performed to demonstrate the influence of different supervision efficiencies and penalties on the evolutionary strategies